2013
DOI: 10.1111/cns.12086
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Progenitor Cells Contribute to Neointima Formation in Rabbit Elastase‐Induced Aneurysm after Flow Diverter Treatment

Abstract: BM-derived EPCs participate in neointima formation and reendothelialization in elastase-induced aneurysm after flow diverter treatment. The EPCs may differentiate into different cell types according to the stages of neointima formation in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 34 publications
(36 reference statements)
3
22
0
1
Order By: Relevance
“…At that location and at 60 days, the FDs were completely covered with tissue and advanced endothelialization was found. Our results are in agreement with Li et al 19 regarding the role of CD34+ PCs in the FD endothelialization process. They transfused fluorescent labeled PCs after FD implantation and were later able to identify them on the surface of the FDs.…”
Section: Discussionsupporting
confidence: 94%
“…At that location and at 60 days, the FDs were completely covered with tissue and advanced endothelialization was found. Our results are in agreement with Li et al 19 regarding the role of CD34+ PCs in the FD endothelialization process. They transfused fluorescent labeled PCs after FD implantation and were later able to identify them on the surface of the FDs.…”
Section: Discussionsupporting
confidence: 94%
“…ECFCs, a unique population of EPCs, possess high proliferation, self-renewal and in vivo vasculogenic potential (Melero-Martin et al, 2007;Richardson and Yoder, 2011), which show good promise in application of vessel repair (Lavergne et al, 2011). In this study, we found successive ECFCs transfusion retarded CA wall degeneration upon homing to aneurysmal wall (Fang et al, 2012;Li et al, 2013). Growing evidence suggests that degeneration of vessel wall followed by vascular remodeling and aneurysm enlargement is associated with CA prone to rupture (Aoki et al, 2008a; Kataoka et al, 1999).…”
Section: Discussionsupporting
confidence: 50%
“…Frosen et al (19) demonstrated that endothelial and neointimal cells were mostly originated from the aneurysm wall, with only a minor contribution from the bone marrow in a mouse model of saccular aneurysm. Li et al (20) transfused fluorescence-labeled cultured endothelial progenitor cells in rabbits treated with flow diverters and observed fluorescence-positive endothelial progenitor cells in the subendothelial space and around flow diverter struts. However, in our immunohistochemical analysis, we did not notice any CD34-positive cells, suggesting that the endothelial cells do not originate from the circulating progenitor cells.…”
Section: Experimental Studies: Cellular Mechanisms Of Aneurysm Occlusmentioning
confidence: 99%